2013
DOI: 10.1309/ajcpjtwk07fsabrj
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive RNA In Situ Hybridization for Detection of Restricted Clonal Expression of Low-Abundance Immunoglobulin Light Chain mRNA in B-Cell Lymphoproliferative Disorders

Abstract: BRISH analysis of κ and λ immunoglobulin mRNA expression is a sensitive tool for establishing LCR in B-cell NHL when FCM results are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…Initially, this staining seemed to suggest conflicting results, particularly in the cases which had clear KAPPA mRNA cytoplasmic black colored staining while having apparent " LAMBDA " pink staining in the nucleoli of the same cells. However, a review of the literature revealed that this staining pattern may result from cross hybridization with the Ig lambda-like polypeptide 5 ( IGLL5 ) gene on chromosome 22, which is located within the immunoglobulin lambda locus but does not require somatic rearrangement for expression, meaning that it can be expressed in non-Ig expressing, non-B, cells [13]. As recently demonstrated by Tubbs et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, this staining seemed to suggest conflicting results, particularly in the cases which had clear KAPPA mRNA cytoplasmic black colored staining while having apparent " LAMBDA " pink staining in the nucleoli of the same cells. However, a review of the literature revealed that this staining pattern may result from cross hybridization with the Ig lambda-like polypeptide 5 ( IGLL5 ) gene on chromosome 22, which is located within the immunoglobulin lambda locus but does not require somatic rearrangement for expression, meaning that it can be expressed in non-Ig expressing, non-B, cells [13]. As recently demonstrated by Tubbs et al .…”
Section: Discussionmentioning
confidence: 99%
“…As recently demonstrated by Tubbs et al . cross-hybridization with the LAMBDA CISH probe occurs because while the first exon of IGLL5 gene is unrelated to immunoglobulin variable genes, the second and third exons use the same loci as the Ig-lambda joining 1 and the Ig-lambda constant 1 gene segments [13,14]. Recognition of this non-specific pattern allowed interpretation of cases with pink nucleolar staining as well as black cytoplasmic staining as KAPPA restricted.…”
Section: Discussionmentioning
confidence: 99%
“…We then further used an ultrasensitive RNAscope in situ hybridization (ISH) method to detect and quantify low densities of CB 2 R mRNA expression in brain slices of rats and mice since the traditional ISH method may not be sensitive enough to detect the low CB 2 R mRNA in rodent brains (Tubbs et al, 2013;Wang et al, 2012). Figure 5A shows mouse and rat coronal atlas, illustrating PFC, VTA, DST and NAc.…”
Section: Rnascope In Situ Hybridization Of Cb 2 R In Rat and Mouse Brmentioning
confidence: 99%
“…Visualization of RNA transcripts for TNF-a, transforming growth factor (TGF)-b, IFN-g, IL-17A, IL-16, IL-10, CXCL9 and CXCL10 was done according to the manufacturer's instructions for RNAScope Ò 2.0 (Wang et al, 2012;Tubbs et al, 2013). A proprietary probe combination was used for each of the cytokine and chemokine mRNAs.…”
Section: Rna Chromogenic In-situ Hybridizationmentioning
confidence: 99%